Changes of National Structure of the Czech Lands - Historical Outline and Legislative Framework from 1945 to the Present - Krákora, Pavel; Nováková, Zdenka (Civilia, 2017)
This text deals with the problems of shaping national structure of the Czech Lands. It is mentioned primarily historical context with beginning of German's colonization of border (peripheral) areas of the Czech Lands in 13th century and later competitions Czechs and Germans during 19th and the first half of 20th century. In next part of the text are following changes of national structure after 1945 (Czechoslovakia with regard to Czech Lands) to the present including legislative point of views.
Keywords: National minorities; Czech Lands; Czechoslovakia; Czech Republic; History; Present; Czechs; Germans; Legislative Framework